Reformation as an Inspiration for Reforms of the Eastern Churches in the Polish-Lithuanian Commonwealth - WEREDA, Dorota (Historia i Świat, 2018)
The Reformation was a phenomenon influencing transformations of the Orthodox Church and the Uniate Church in the multi-denominational Polish-Lithuanian state. In response to a particularly severe lack of education compounded by the influence of the Reformation in the Easter Churches, certain educational initiatives were undertaken, translation of the Bible and liturgical texts into the Old Orthodox Church Slavonic language, acquainting people with new forms and ways of religious apologetics. Ideas initiated by the Reformation were developed in the 16th century by Piotr Mohyła. Under the influence of the Reformation a new quality of relationships and social bonds was created in the Orthodox Church society of the Polish-Lithuanian Commonwealth. The activities of laymen and Orthodox Church fraternities became more intensified. The ideas of the Reformation on soteriological subjects became an inspiration for part of Orthodox Church elites to enter into union with the Papacy.